(untitled) (Muitas Vozes, 2021)
In this paper, the analysis focuses on the elucidation of how is the refiguration of the protagonist Graciliano Ramos, in the novel Em liberdade: uma ficção de Silviano Santiago (At liberty: a fiction by Silviano Santiago), and how it serves to feed the survival of this historical literature figure. The study of the narrator and the protagonist, and their figurations, was carried out in order to understand the human format of the protagonist. Attention was paid to the perspectives that appear and are related in the narrative, interconnected to the voices of the narrators and the characters, which contribute to the construction and problematization of Ramos’s identity. It was possible to trace who “Gracilviano” is and his ways of living with others and positioning himself before the world.